CHEMICAL COMPOSITION AND FEEDING VALUE OF VEGETABLE WASTES COLLECTED FROM PALU TRADITIONAL MARKETS AS FEED COMPONENT OF RUMINANTS - Marsetyo; I Wayan Sulendre (Journal of Islamic, Social, Economics and Development, 2023)
Two studies were done to identify chemical content of vegetable waste (VW) from Palu markets (study 1) and to examine the effect of VW level inclusion in the diet on total dry matter intake (DMI), dry matter digestibility (DMD), average daily gain (ADG) and income over feed cost (IOFC) of Kacang goat received with rice bran (RB) (study 2). In study2, there were 4 treatments and 6 replications in a completely randomized block design. The treatment include RB plus corn stover, RB plus CS:VW (80:20), RB plus CS:VW (60:40), RB plus CS:VW (40:60, all are ad libitum.Total VW collected from Palu markets was 46.931 kg/months.Dry matter (DM), organic matter (OM), crude protein (CP), and crude fibre (CF) of VW were variable with the range of 10.32-25.36; 85.33-91.87;2.80-25.85; and 4.23-46.29%, respectively.Goat received RB plus CS:VW (40:60) ad libitum had the highest total DMI,DMD, LWG and IOFC value.It was concluded that VW can be included in goat diet up to 60% with high profitability.